Photoresponsive Multirole Nanoweapon Camouflaged by Hybrid Cell Membrane Vesicles for Efficient Antibacterial Therapy of Pseudomonas aeruginosa‐Infected Pneumonia and Wound - Hening Liu; Lu Tang; Yue Yin; Yuqi Cao; Cong Fu; Jingwen Feng; Yan Shen; Wei Wang (Advanced Science)
Abstract Exploring effective antibacterial approaches for targeted treatment of pathogenic bacterial infections with reduced drug resistance is of great significance. Combinational treatment modality that leverages different therapeutic components can improve the overall effectiveness and minimize adverse effects, thus displaying considerable potential against bacterial infections. Herein, red blood cell membrane fuses with macrophage membrane to develop hybrid cell membrane shell, which further camouflages around drug‐loaded liposome to fabricate biomimetic liposome (AB@LRM) for precise antibacterial therapy. Specifically, photoactive agent black phosphorus quantum dots (BPQDs) and classical antibiotics amikacin (AM) are loaded in AB@LRM to accurately target the inflammatory sites through the guidance of macrophage membrane and long residence capability of red blood cell membrane, eventually exerting efficacious antibacterial activities. Besides, due to the excellent photothermal and photodynamic properties, BPQDs act as an efficient antibacterial agent when exposed to near‐infrared laser irradiation, dramatically increasing the sensitivity of bacteria to antibiotics. Consequently, the synergistic sterilizing effect produced by AB@LRM further restricts bacterial resistance. Upon laser irradiation, AB@LRM shows superior anti‐inflammatory and antibacterial properties in models of P. aeruginosa‐infected pneumonia and wounds. Hence, this light‐activatable antibacterial nanoplatform with good biocompatibility presents great potential to advance the clinical development in the treatment of bacterial infections.